The role of work team behaviors in achieving organizational excellence - Assist. Lec. Ahmed Amer Kazem; Assist. Lec. Muhanned Salam Jawad; Assist. Lec. Reza Naem Hussien (Zien Journals, 2023)
The purpose of the research is to examine teamwork behaviors and how they affect organizational excellence. The objective is to investigate the connection and influence between organizational excellence at the studied university and work team behaviors. With the help of a representative sample of administrative leaders, specifically the heads of the scientific and administrative departments at Maysan University, this will be accomplished by developing a hypothetical model based on two assumptions of correlation and impact., employing a variety of statistical techniques. The most significant conclusion drawn from the results is that work team behaviors, such as team coordination, cohesiveness, and effectiveness, are correlated with and have an impact on achieving organizational excellence at the institution. On the basis of this, a number of recommendations were put up, the most crucial of which stressed the necessity for the university's top leadership to engage with the teams already in place at the researched colleges by actively participating in the teams' tasks. This is critical for boosting staff morale and motivation as well as closing the gap between upper and lower management
Keywords: Teamwork behaviors; Organizational excellence; team Coordination